2014
DOI: 10.3389/fonc.2014.00222
|View full text |Cite
|
Sign up to set email alerts
|

Src: Marker or Actor in Prostate Cancer Aggressiveness

Abstract: A key question for urologic practitioners is whether an apparently organ-confined prostate cancer (PCa) is actually aggressive or not. The dilemma is to specifically identify among all prostate tumors the very aggressive high-grade cancers that will become life-threatening by developing extra-prostatic invasion and metastatic potential and the indolent cancers that will never modify a patient’s life expectancy. A choice must be made between several therapeutic options to achieve the optimal personalized manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 107 publications
(149 reference statements)
1
31
0
Order By: Relevance
“…Numerous previous studies addressing SFKs in the prostate focussed on oncologic context (Cai et al, ; Montero et al, ; Varkaris et al, ; Vlaeminck‐Guillem et al, ). In prostate cancer cells, SFKs may promote migration, which depends on actin dynamics and cytoskelet organization (Slack et al, ; Sabbota et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies addressing SFKs in the prostate focussed on oncologic context (Cai et al, ; Montero et al, ; Varkaris et al, ; Vlaeminck‐Guillem et al, ). In prostate cancer cells, SFKs may promote migration, which depends on actin dynamics and cytoskelet organization (Slack et al, ; Sabbota et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Src kinase is another important player in the EMT process as it is activated by several neuropeptides, including CgA, NSE, serotonin, neurophysin, bombesin, and synaptophysin. Through direct physical interaction with the AR, Src is able to phosphorylate the AR and thereby induce ligand-independent AR activation (one of the key mechanisms of castration-resistant PC) ( 38 ). Neuropeptides, notably bombesin were also found to enhance early growth response 1 (Egr-1) expression leading to increased human protease-activated receptor 1 (PAR1) expression and function directly correlating with invasiveness and the degree of PC malignancy ( 39 ).…”
Section: Emerging Molecular Targets Within the Landscape Of Nepc Diffmentioning
confidence: 99%
“…Although the identification and development of more specific diagnostic biomarkers are considered important, the major focus in translational prostate cancer research is the identification of potential “quantitative variables” to detect clinically significant prostate cancers. As reported by Vlaeminck-Giullem et al ( 10 ), the current dilemma is to specifically distinguish among all prostate tumors the very aggressive high-grade cancers that will become life threatening by developing extra-prostatic invasion and metastatic potential from the indolent cancers that will never modify a patient’s life expectancy. At molecular level, Src and other members of the Src kinase family have been proposed as potential candidates ( 10 ).…”
mentioning
confidence: 99%
“…As reported by Vlaeminck-Giullem et al ( 10 ), the current dilemma is to specifically distinguish among all prostate tumors the very aggressive high-grade cancers that will become life threatening by developing extra-prostatic invasion and metastatic potential from the indolent cancers that will never modify a patient’s life expectancy. At molecular level, Src and other members of the Src kinase family have been proposed as potential candidates ( 10 ). Recently, it has been shown that the activation of Src-dependent intracellular pathways is frequently observed in clinically significant prostate cancer ( 11 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation